Clinical and radiological evaluation of breast polyneoplasms - N. I. Rozhkova; I. M. Frolov (ABV-press, 2014)
Background. The past decades have been marked by a rise in the incidence of polyneoplasia (PNP), including that of the breast, which necessitates a more in-depth analysis of its manifestations.Materials and methods. The study was based on the results of a complex radiological and postmortem examination in 120 women with different types of breast PNP (BPNP) and 6 with metastatic breast lesion.Results. The procedure for radiological and postmortem studies in BPNP was improved; the optimal diagnostic complex developed; and the radiation semiotics of different types of BPNP clarified.Conclusion. Overall, the comprehensive approach to the examination to be made by one specialist who can use a broad spectrum of vari- ous procedures and competent in allied specialties has allowed the objective criteria for BPNP to be defined.